Clinical Profile and Treatment of Acne Vulgaris Patients - M. Yulianto Listiawan; Farah Meriana Fajrin; Rahmadewi Rahmadewi; Afif Hidayati; Sawitri Sawitri; Diah Mira Indramaya; Rebekah Juniati Setiabudi; Maya Wardiana (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Acne vulgaris (AV) is not a deadly condition may affect one’s quality of life. Treatment of AV includes topical and oral, depending on the severity. Antibiotics as oral treatment should not be given alone because it can precipitate resistance. Purpose: To describe the clinical characteristics of AV in a tertiary hospital in Indonesia and evaluate the treatment given. Methods: This is a descriptive, retrospective study with a cross-sectional design. The study subject was classified based on severity according to Plewig and Kligman’s acne grading. Further evaluation was made according to the type of lesion, the risk factortopical and oral treatment in subjects with grades 2, 3, and 4. This research was conducted at the Cosmetic Medic Division, Dermatology and Venereology Outpatient Clinic at Dr. Soetomo General Academic Hospital Surabaya based on medical records from the period of 2017 to 2019. Result: From 2017 to 2019, there were 525 (1.1%) new AV patients out of a total of 45,754 new patients. AV was the major diagnosis in the Cosmetic Medic division. AV grades 2, 3, and 4 were found in 167 patients (32.0%). The most common lesion was papulopustular (75.4%) and the most common risk factor was hormonal (58.7%). All the patients received tretinoin, clindamycin gel 1.2%, and sunscreen for topical treatment. Doxycycline was the most common oral antibiotic used (98.2%) Conclusion: The most common AV grade in this study was mild AV. Oral antibiotics were given to moderate-to-severe AV patients in combination with topical treatment to prevent resistance.